Magnetic nanoparticles enhance the anticancer activity of cathelicidin LL-37 peptide against colon cancer cells - Niemirowicz K (Dove Medical Press, 2015)
Katarzyna Niemirowicz,1 Izabela Prokop,2 Agnieszka Z Wilczewska,3 Urszula Wnorowska,1 Ewelina Piktel,1 Marzena Wątek,4 Paul B Savage,5 Robert Bucki1,6 1Department of Microbiological and Nanobiomedical Engineering, Medical University of Bialystok, 2Department of Medicinal Chemistry, Medical University of Bialystok, 3Institute of Chemistry, University of Bialystok, Bialystok, 4Department of Hematology, Holy Cross Oncology Center of Kielce, Kielce, Poland; 5Department of Chemistry and Biochemistry, Brigham Young University, Provo, UT, USA; 6Department of Physiology, Pathophysiology and Microbiology of Infections, The Faculty of Health Sciences of the Jan Kochanowski University in Kielce, Kielce, Poland Abstract: The pleiotropic activity of human cathelicidin LL-37 peptide includes an ability to suppress development of colon cancer cells. We hypothesized that the anticancer activity of LL-37 would improve when attached to the surface of magnetic nanoparticles (MNPs). Using colon cancer culture (DLD-1 cells and HT-29 cells), we evaluated the effects of MNPs, LL-37 peptide, its synthetic analog ceragenin CSA-13, and two novel nanosystems, ie, MNP@LL-37 and MNP@CSA-13, on cancer cell viability and apoptosis. Treatment of cancer cells with the LL-37 peptide linked to MNPs (MNP@LL-37) caused a greater decrease in cell viability and a higher rate of apoptosis compared with treatment using free LL-37 peptide. Additionally, we observed a strong ability of ceragenin CSA-13 and MNP@CSA-13 to induce apoptosis of DLD-1 cells. We found that both nanosystems were successfully internalized by HT-29 cells, and cathelicidin LL-37 and ceragenin CSA-13 might play a key role as novel homing molecules. These results indicate that the previously described anticancer activity of LL-37 peptide against colon cancer cells might be significantly improved using a theranostic approach. Keywords: anticancer activity, colorectal cancer, ceragenin, cathelicidin LL-37, magnetic nanoparticles